German general practitioners’ experiences during the COVID-19 pandemic and how it affected their patient care: A qualitative study - Lisa Makowski; Hanna Schrader; Sandra Parisi; Jana Ehlers-Mondorf; Stefanie Joos; Hanna Kaduszkiewicz; Ildikó Gágyor (European Journal of General Practice, 2023)
AbstractBackground General practitioners (GPs) play a significant role in providing medical care to patients affected by the coronavirus disease 2019 (COVID-19). Little is known about the impact of the pandemic on patient care from the perspective of GPs.Objectives To gain insight into GPs’ experiences of the COVID-19 pandemic and its impact on patient care in Germany.Methods From August to December 2020, qualitative, semi-structured telephone interviews were conducted with 22 GPs from four randomly selected federal states in Germany. We analysed the data according to Kuckartz’s method of content analysis.Results Five themes emerged: changes in healthcare system, practice routines, patient care, personal life, and improving health crisis preparedness. Communication with authorities and following rapidly changing guidelines were the biggest challenges during the pandemic. Teamwork and collegial exchange in the practice were seen as important sources of support to overcome these barriers. Participants stated that they managed to secure care but expressed concerns about how social distancing might affect the doctor-patient relationship. In their professional and private lives, GPs perceived themselves as role models with a high responsibility for the health of others. Consistent guidance by health authorities and reliable information were raised as necessary for managing patient care in the pandemic.Conclusion Findings show that patient care was successful but GPs’ adaptation to unprecedented conditions was limited by poor communication and collaboration with health authorities. Therefore, providing adequate support services by policymakers is essential to strengthen primary care in future health crises.